Enhanced filmwise condensation heat transfer with novel pin fin surfaces fabricated by selective laser melting - Lam, Yiyin (2018)
This report examines the filmwise condensation heat transfer performance of ten sinuous pin fin surfaces fabricated by Selective Laser Melting (SLM). The experiments were conducted using steam at low vapour velocity of 0.6 m/s to replicate the assumptions made in Nusselt’s film theory. The sinuous pin fin surfaces have the same fin diameter of 1240 μm, but different fin pitches (p of 1250 μm, 1667 μm and 2500 μm) and different fin heights (l of 1245 μm, 1661 μm, 2491 μm and 3321 μm). The aim is to study the effects of fin pitch and fin height on the condensation heat flux and determine the best surface enhancement. The condensate retention of each specimen was also investigated to study its relation to the fin density. The results showed that all sinuous pin fin surfaces had considerable enhancement of condensation heat transfer performance as compared to a plain surface. The results also showed that even though increasing the fin height and decreasing the fin pitch led to greater heat transfer area, it did not always translate to better condensation heat transfer performance due to factors such as condensate flooding and lower fin efficiency of the taller fins. The reduction in fin efficiency with increasing fin height thus limits the extent to which the fin height can be increased. In this study, the fin height (l) of 1661 μm was determined as the most optimal height in promoting condensation. The decrease in fin pitch (p) also led to an increase in heat transfer coefficient (h), but an optimal fin pitch exists where further decrease in fin pitch only lead to a marginal increase in h. In this study, p of 1667 μm was deduced as the most efficient fin pitch. Overall, the greatest heat flux enhancement of 1.94 was achieved with specimen S2a, with p of 1250 μm and l of 1661 μm, while specimen S1c, with p of 2500 μm and l of 1245 μm, exhibited the greatest heat-flux-to-area enhancement ratio of 1.17, Moreover, it was found that fin height had negligible effect on the condensate retention, and sinuous pin fin surfaces of the same fin density had the same level of condensate retention. Lastly, in comparison with the cylindrical pin fin surface investigated by Ho and Leong [1], the S2a specimen showed better condensation heat transfer performance despite having 2 times smaller heat transfer area. This can be attributed mainly to the effectiveness of the surface tension effect of the sinuous pin fin geometry.